Large centric diatoms allocate more cellular nitrogen to photosynthesis to counter slower RUBISCO turnover rates - Wu, Yaping; Jeans, Jennifer; Suggett, David J.; Finkel, Zoe V.; Campbell, Douglas A. (Frontiers in Marine Science, 2014)
Diatoms contribute ~40% of primary production in the modern ocean and encompass the largest cell size range of any phytoplankton group. Diatom cell size influences their nutrient uptake, photosynthetic light capture, carbon export efficiency, and growth responses to increasing pCO2. We therefore examined nitrogen resource allocations to the key protein complexes mediating photosynthesis across six marine centric diatoms, spanning 5 orders of magnitude in cell volume, under past, current and predicted future pCO2 levels, in balanced growth under nitrogen repletion. Membrane bound photosynthetic protein concentrations declined with cell volume in parallel with cellular concentrations of total protein, total nitrogen and chlorophyll. Larger diatom species, however, allocated a greater fraction (by 3.5 fold) of their total cellular nitrogen to the soluble RUBISCO carbon fixation complex than did smaller species. Carbon assimilation per unit of RUBISCO large subunit (C RbcL-1 s-1) decreased with cell volume, from ~8 to ~2 C RbcL-1 s-1 from the smallest to the largest cells. Whilst a higher allocation of cellular nitrogen to RUBISCO in larger cells increases the burden upon their nitrogen metabolism, the higher RUBISCO allocation buffers their lower achieved RUBISCO turnover rate to enable larger diatoms to maintain carbon assimilation rates per total protein comparable to small diatoms. Individual species responded to increased pCO2, but cell size effects outweigh pCO2 responses across the diatom species size range examined. In large diatoms a higher nitrogen cost for RUBISCO exacerbates the higher nitrogen requirements associated with light absorption, so the metabolic cost to maintain photosynthesis is a cell size-dependent trait.